OSL Age Determination of Archaeological Stone Structures Using Trapped Aeolian Sediments: A Case Study from the Negev Highlands, Israel. Issue 6 (21st June 2016) - Junge, Andrea; Lomax, Johanna; Shahack‐Gross, Ruth; Dunseth, Zachary C.; Finkelstein, Israel; Fuchs, Markus
Abstract : Optically stimulated luminescence (OSL) dating is widely applied to sediments in paleoenvironmental sciences. However, there are only limited examples determining the age of archaeological stone structures by OSL using dust deposits. The age of dust deposits associated with ancient buildings may be used to date the onset of settlement (sediment below structures), settlement activity (occupation layer), or the time after a settlement had been abandoned or destroyed (sediment between collapsed roofs and walls). In this study, OSL dating is applied to establish numerical dates for settlement structures situated in the Negev Highlands, Israel. Two archaeological sites are investigated to identify their occupation history, by dating nine samples of aeolian dust trapped within the remains of ancient buildings. The OSL dating technique is applied using coarse grain quartz and a standard single‐aliquot regenerative‐dose (SAR) protocol. It was possible to date the onset of sedimentation in a later phase of the human occupation or shortly after the sites were abandoned, to 3.7 ± 0.3 ka (Intermediate Bronze Age) at the central site and to 2.7 ± 0.2 ka (Iron Age) at the ephemeral site. These results are supported by archaeological evidence gained from pottery finds and the architecture of the ancient buildings.